(untitled) (Journal of Pathology of Nepal, 2021)
Background: Sodium fluoride tubes or serum separator tubes are mostly used for blood glucose estimation in the clinical laboratories of Nepal. The study aimed to investigate the stability of glucose in samples collected in serum separator tubes and sodium fluoride/sodium ethylenediaminetetraacetic tubes by comparing the glucose concentration at 30 minutes and 4 hours collected and handled differently to simulate prolonged sample transport between venipunctures, centrifugation, and measurement. Materials and Methods: Samples were collected from healthy volunteers into two different serum separator tubes and two different sodium fluoride/sodium ethylenediaminetetraacetic tubes. Glucose concentration was measured at 30 minutes after venipuncture and compared with results from the same samples analyzed at four hours and with the results from tubes centrifuged with a delay of 4 hours. Differences between baseline and respective delayed analyzed glucose values for each tube type were tested using the Student’s paired t-test and Deming regression. Results: When comparing plasma glucose at 30 minutes, glycolysis caused a relative reduction of the glucose concentration in serum at 30 minutes of 3.1 %, which is only slightly less than at 4 hours (3.7 %). This is still substantially more than the reduction in plasma at 4 hours (1.3 %). Surprisingly, the difference between plasma glucose at 30 minutes and serum glucose at 4 hours was only 1.9% which is not clinically significant. Conclusions: The Na-F/Na2 EDTA tubes and serum separator tubes can be used interchangeably for analysis of blood glucose up to 4 hours if centrifuged within 30 minutes.